Sex Objects and Conquered People? Representations of women in Nigerian Films in the 21st Century - Agwu A. Ejem; Ifeanyi M. Nwokeocha; Jude O. Abba Father; Nkem Fab-Ukozor; Chinedu Ibekwe (QISTINA: Jurnal Multidisiplin Indonesia, 2022)
This study examined the subjugation and objectification of women in Nigerian films produced in the 21st Century to determine whether the representations of women have changed at the turn of the Century. The objectives of this study were to find out the extent of subjugation of women in Nollywood films in the 21st Century and determine the extent of objectification of women in Nollywood films in the 21st Century. This study was anchored on the feminist muted group theory. The design adopted was a mixed-method approach that combined content analysis and in-depth interviews. The researchers focused on Nollywood films produced from 2000 to 2021 that have women playing leading or supporting roles. A total of 22 films were coded and eleven film experts and scholars were interviewed. It was found that women were not significantly subjugated in Nigerian films produced in the 21st century. However, women are still highly sexually objectified in Nigerian films produced in the 21st century. They are portrayed in a way that viewers can make judgments about them based on their physical appearance and their sex appeal. It was recommended that the Nigerian Film and Video Censors' Board must play its part in reducing the incidence of female objectification in Nigerian films by putting Objectification (O) as a film classification element, in the same breath as Nudity, Strong Language, and Violence (NSL).